2012
DOI: 10.1039/c2sm25588j
|View full text |Cite
|
Sign up to set email alerts
|

Wormlike core–shell nanoparticles formed by co-assembly of double hydrophilic block polyelectrolyte with oppositely charged fluorosurfactant

Abstract: Formation of polyelectrolyte-surfactant complexes (PE-S) between an anionic polyelectrolyte, poly(sodium 2-sulfamate-3-carboxylate isoprene)-block-poly(ethylene oxide) (PSCI-PEO) and a cationic fluorosurfactant, N-(

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 33 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…Typically around charge equimolarity one observes an extended region of precipitate formation, while for an excess of surfactant or polyelectrolyte, solutions containing complexes are observed. This strong synergistic interaction is driven by the release of the counterions [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. The study of such systems is not only of great scientific interest but they also have many applications e.g., in cosmetics, detergency and drug delivery [2,[17][18][19].…”
mentioning
confidence: 99%
“…Typically around charge equimolarity one observes an extended region of precipitate formation, while for an excess of surfactant or polyelectrolyte, solutions containing complexes are observed. This strong synergistic interaction is driven by the release of the counterions [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. The study of such systems is not only of great scientific interest but they also have many applications e.g., in cosmetics, detergency and drug delivery [2,[17][18][19].…”
mentioning
confidence: 99%
“…Protonation of the PDMPA block took place at pH 2, hence surfactant monomers bind to the polycation block. This leads to charge neutralization and consequent formation of wormlike micelles, which are not possible in pure SDS or polymer solution at the same conditions [67]. A worm-like structure was obtained due to binding of SDS molecules to the protonated polyelectrolyte block and promotion of other surfactant molecules to bind the nearest neighboring sites through a hydrophobic association between hydrophobic surfactant tails.…”
Section: Cryo-temmentioning
confidence: 98%
“…The concept was further extended to diblock copolymers comprising of a polyelectrolyte and a neutral water soluble block. The interaction of the polyelectrolyte block with an oppositely charged surfactant induces hydrophobicity in the polyelectrolyte block and micelles form with core of polyelectrolyte-surfactant (P-S) complex and stabilized by the soluble shell of neutral hydrophilic block of copolymer in aqueous medium [65][66][67]. Therefore, our objective was to examine the complex formation of protonated PNIPAM 127 -b-PDMPA 31 with SDS (0.15 wt.%) at a wide pH range and at 0.15 wt.% copolymer concentration.…”
Section: Fluorescencementioning
confidence: 99%
“…SAXS, cryogenic TEM and AFM were employed to investigate the structure of synthesized PEÀ S, revealing wormlike core-shell nanoparticles. [41] Li [42] et al reported caterpillar-like micelles via selfassembly of amphiphilic linear-block-dendritic copolymers, synthesizing three block copolymers containing acrylic acid and methyl methacrylate. These polymers contained three topologies such as double linear blocks, poly(acrylic acid) (PAA) linear block/poly(methyl methacrylate) (PMMA) G1dendron and PAA linear block/PMMA G2-dendron, which were characterized by NMR, FTIR and gel permeation chromatography techniques.…”
Section: Hierarchically Self-assembled Caterpillar-like Superstructuresmentioning
confidence: 99%
“…They synthesized the polyelectrolyte‐surfactant complexes (PE−S) from anionic and cationic materials such as anionic polyelectrolyte, poly(sodium 2‐sulfamate‐3‐carboxylate isoprene)‐block‐poly(ethylene oxide) (PSCI‐PEO) and a cationic fluoro‐surfactant, N‐(3,3,4,4,5,5,6,6,7,7,8,8,9,9,10,10,10‐heptadecafluorodecyl) pyridinium chloride (HFDPCl), and investigated their static, dynamic and electrophoretic light scattering properties. SAXS, cryogenic TEM and AFM were employed to investigate the structure of synthesized PE−S, revealing wormlike core‐shell nanoparticles [41] …”
Section: Introductionmentioning
confidence: 99%